2018
DOI: 10.1038/s41416-018-0179-6
|View full text |Cite
|
Sign up to set email alerts
|

25-hydroxyvitamin D serum levels in patients with high risk resected melanoma treated in an adjuvant bevacizumab trial

Abstract: In this stage II/III melanoma cohort, vitamin D did not correlate with known prognostic markers, nor predict for DFI or OS, but there was some evidence of benefit for patients with stage II disease treated with bevacizumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…Subsequent studies confirmed that a lower vitamin D level was related to greater progression of melanoma [Breslow thickness, Clark level, the American Joint Committee on Cancer (AJCC) stage], the presence of poor prognostic markers (ulceration, higher mitotic index), shorter overall survival and increased risk for melanoma-specific death (222)(223)(224)(225)(226). However, some investigators (227) did not observe such relationships and found only longer disease-free survival for patients with higher vitamin D levels. Melanoma risk is related to a higher number of nevi, however Ribero and coworkers showed positive correlation of serum vitamin D level and nevi count (228).…”
Section: Serum Vitamin D Level In Patients With Melanomamentioning
confidence: 99%
“…Subsequent studies confirmed that a lower vitamin D level was related to greater progression of melanoma [Breslow thickness, Clark level, the American Joint Committee on Cancer (AJCC) stage], the presence of poor prognostic markers (ulceration, higher mitotic index), shorter overall survival and increased risk for melanoma-specific death (222)(223)(224)(225)(226). However, some investigators (227) did not observe such relationships and found only longer disease-free survival for patients with higher vitamin D levels. Melanoma risk is related to a higher number of nevi, however Ribero and coworkers showed positive correlation of serum vitamin D level and nevi count (228).…”
Section: Serum Vitamin D Level In Patients With Melanomamentioning
confidence: 99%
“…Thus, several studies have shown that vitamin D deficiency impairs the macrophage and/or NK cell-mediated cytotoxicity of Rituximab (anti-CD20) in diffuse large B-cell, follicular, and Burkitt lymphoma patients [ 288 , 290 , 291 ], and of Cetuximab (anti-EGFR) in colon cancer cell lines [ 292 ]. In addition, some evidence of benefit has been observed in breast cancer patients treated with Trastuzumab (anti-HER2) and in melanoma patients treated with Bevacizumab (anti-VEGF) [ 290 , 293 ].…”
Section: Mechanisms Introductionmentioning
confidence: 99%
“…Pre-treatment with vitamin D analogues potentiates TNF-α cytotoxic effects through impaired cell viability as well as DNA fragmentation (26). Synergism has also been reported between vitamin D and tamoxifen (42), histone deacetylase inhibitors (43), paclitaxel (44), dacarbazine and cisplatin (45), 5-fluorouracil (5-FU) (46), bevacizumab (47), immune checkpoint inhibitors (48), and the nutraceutical S-adenosylmethionine (SAM).…”
Section: Resultsmentioning
confidence: 99%